Critical role of glutamatergic and GABAergic neurotransmission in the central mechanisms of theta‐burst stimulation. Issue 6 (1st January 2019) - Li, Cheng‐Ta; Huang, Ying‐Zu; Bai, Ya‐Mei; Tsai, Shih‐Jen; Su, Tung‐Ping; Cheng, Chih‐Ming
Abstract: Theta‐burst stimulation (TBS) is a varied form of repetitive transcranial magnetic stimulation (rTMS) and has more rapid and powerful effects than rTMS. Experiments on the human motor cortex have demonstrated that intermittent TBS has facilitatory effects, whereas continuous TBS has inhibitory effects. Huang's simplified model provides a solid basis for elucidating such after‐effects. However, evidence increasingly indicates that not all after‐effects of TBS are as expected, and high variability among individuals has been observed. Studies have suggested that the GABAergic and glutamatergic neurotransmission play a vital role in the aforementioned after‐effects, which might explain the interindividual differences in these after‐effects. Herein, we reviewed the latest findings on TBS from animal and human experiments on glutamatergic and GABAergic neurotransmissions in response to TBS. Furthermore, an updated theoretical model integrating glutamatergic and GABAergic neurotransmissions is proposed.